2006
DOI: 10.1007/s11104-006-9018-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and mobility of manganese in the hyperaccumulator plant Phytolacca acinosa Roxb. (Phytolaccaceae)

Abstract: The distribution and mobility of manganese (Mn) in the hyperaccumulator plant species Phytolacca acinosa Roxb. (Phytolaccaceae) were investigated in a hydroponic system. The plants were exposed to 2 or 5 mM Mn for up to 28 days. For any given plant, the Mn content in the mature leaves (nos. 5-9) was always higher than that in the old (nos. 1-4) and young leaves (nos. 10-14). Within the different parts of a leaf, Mn was preferentially accumulated in the leaf marginal area, where the observed level was threefold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 28 publications
3
24
1
Order By: Relevance
“…Our attempt to localise these substances by isolating protoplast and vacuole was unsuccessful. In our previous studies, we found that the highest Mn concentration occurred in the supernatant fraction (after centrifugation at 20,000g for 45 min) using a cell fractionation analysis method (Xu et al 2006). This fraction corresponded to the vacuolar and cytoplasm (excluding the organelles) fraction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our attempt to localise these substances by isolating protoplast and vacuole was unsuccessful. In our previous studies, we found that the highest Mn concentration occurred in the supernatant fraction (after centrifugation at 20,000g for 45 min) using a cell fractionation analysis method (Xu et al 2006). This fraction corresponded to the vacuolar and cytoplasm (excluding the organelles) fraction.…”
Section: Discussionmentioning
confidence: 96%
“…This fraction corresponded to the vacuolar and cytoplasm (excluding the organelles) fraction. Since the vacuole occupies~95% of the total volume of a mature plant cell (Memon and Yatazawa 1984), it could be inferred that most of the Mn found in the supernatant fraction might derive from the vacuoles (Xu et al 2006). Organic acids are also known to accumulate in plant vacuoles (Ryan et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Well-known Mn hyperaccumulators, plants capable of acquiring more than 10,000 mg kg −1 of Mn (dry weight) in its aboveground biomass (Xu et al 2006), include the Gossia bidwillii and Austromyrtus bidwillii from Eastern Australia (Bidwell et al 2002;Fernando et al 2006a), nine species listed by Reeves and Baker, and an unidentified Eugenia species described by Sabah (Proctor et al 1989). In addition, Japan is well known for the accumulator Eleutherococcus sciadophylloides that can sequester up to 7,900 mg.g −1 Mn in the leaf dry matter (Memon et al 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Between 2002 and 2008, additional Mn hyperaccumulators were discovered in eastern Australia (Bidwell et al, 2002), China (Xue et al, 2004) and Japan (Mizuno et al, 2008), that has now led to recognition of several new species and renewed interest in the phenomenon. To date, the woody species have only been investigated through a series of ecophysiological studies, whereas the two herbaceous Phytolacca (Phytolaccaceae) species have mainly been examined in controlled experiments (Xue et al, 2005; Fernando et al, 2006b; Mizuno et al, 2006; Xu et al, 2006a,b, 2009; Fernando et al, 2007a,b). Unlike their herbaceous metal-hyperaccumulating counterparts, Mn-hyperaccumulating trees and shrubs are extremely slow growing and often difficult to propagate.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to: (a) the discovery of several new Mn hyperaccumulators, which has augmented the overall biogeographic knowledge base of hyperaccumulators by providing new perspective on Mn-accumulating taxa analogous to those with already well-established links to other metals (Baker and Brooks, 1989; Baker et al, 1992; Pollard et al, 2000, 2002; Fernando et al, 2009); (b) the discovery that foliar Mn detoxification varies specifically in a manner possibly unique to Mn hyperaccumulators (Fernando et al, 2008); (c) indication that the physiological mechanisms associated with excess Mn uptake and storage in herbaceous Mn hyperaccumulators are similar to those found in herbaceous hyperaccumulators of other metals (Küpper et al, 2000, 2001; Xu et al, 2006a,b); and (d) the pursuit to identify Mn-specific transporters, particularly in woody species where Mn is compartmentalized in highly localized vacuolar concentrations (T. Mizuno unpublished data).…”
Section: Introductionmentioning
confidence: 99%